Persepsi Siswa terhadap Penggunaan Media Pembelajaran E-Komik pada Mata Pelajaran Ekonomi Kelas X Materi Asuransi di SMA PGRI Betung - Paiman Paiman; Neta Dian Lestari; Ramanata Disurya Zam (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The complexity of insurance topics in high school economics often creates learning difficulties due to the dominance of text-based instructional media with limited visual representation. This study aims to examine students’ perceptions of the use of e-comic media in learning insurance material in Grade X at SMA PGRI Betung. The research employed a descriptive quantitative approach involving 110 students selected through purposive sampling. Data were collected using a structured questionnaire distributed via Google Forms, covering aspects of ease of use, visual attractiveness, usefulness, content depth, and accessibility. The results indicate that students showed a highly positive response to the implementation of e-comic media. The ease and clarity aspect reached 81.38%, while visual attractiveness scored 81.21%, reflecting strong acceptance of the media. Students reported that narrative visualization and communicative language helped them better understand key insurance concepts such as premiums and claims. In addition, the media supported independent learning and was accessible across various digital devices without technical difficulties. These findings suggest that e-comic media can function as an effective instructional tool to support students’ comprehension of complex economic concepts in a more engaging and meaningful way.